2005
DOI: 10.1126/science.1100582
|View full text |Cite|
|
Sign up to set email alerts
|

Requirement of Voltage-Gated Calcium Channel β 4 Subunit for T Lymphocyte Functions

Abstract: Calcium is known to play vital roles in diverse physiological processes, and it is known that voltage-gated calcium channels (Cav) mediate calcium influx in excitable cells. However, no consensus exists on the molecular identity of the calcium channels present in nonexcitable cells such as T lymphocytes. Here, we demonstrate that T lymphocytes express both regulatory beta4 and poreforming Cav1 alpha1 subunits of Cav channels. Cav beta4-mutant T lymphocytes fail to acquire normal functions and display impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The dysfunction includes lethal arrhythmias, webbing of fingers and toes, congenital heart disease, immune deficiency, intermittent hypoglycemia, cognitive abnormalities, and autism (39). Furthermore, another recent report has shown that L-type Ca 2ϩ channels are essential for T lymphocyte functions in mice (40). These recent studies revealed a much wider expression pattern for L-type Ca 2ϩ channel proteins, consistent with our observation here.…”
Section: Ca 2ϩ Channel In Fibroblast Cell Migrationsupporting
confidence: 81%
“…The dysfunction includes lethal arrhythmias, webbing of fingers and toes, congenital heart disease, immune deficiency, intermittent hypoglycemia, cognitive abnormalities, and autism (39). Furthermore, another recent report has shown that L-type Ca 2ϩ channels are essential for T lymphocyte functions in mice (40). These recent studies revealed a much wider expression pattern for L-type Ca 2ϩ channel proteins, consistent with our observation here.…”
Section: Ca 2ϩ Channel In Fibroblast Cell Migrationsupporting
confidence: 81%
“…Recently, the L-type VDCC channel has been implicated in regulation of Ca 2ϩ influx induced by TCR stimulation. 31,40 However, the role of VDCC in intracellular Ca 2ϩ mobilization is unknown. Using the L-type VDCC Ca 2ϩ channel antagonist, nifedipine, and agonist, (Ϯ)-Bay K 8644, in the absence of extracellular Ca 2ϩ , we demonstrate that VDCC is involved in intracellular Ca 2ϩ mobilization ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Wogonin-induced prolonged intracellular Ca 2ϩ release in malignant T cells cannot be explained by an overexpression of CRAC. Recently, the L-type voltage-dependent Ca 2ϩ channel (VDCC), known to mediate Ca 2ϩ mobilization in excitable cells, has been shown to play a critical role in Ca 2ϩ mobilization in nonexcitable cells, including T lymphocytes, 31,40 Because nifedipine, the Ca 2ϩ channel antagonist of L-type VDCC, significantly blocked Wogonininduced apoptosis ( Figure 3C), VDCC might play an important role in regulation of intracellular Ca 2ϩ mobilization. To investigate this possibility, the efficiency of nifedipine on blocking intracellular Ca 2ϩ release in Jurkat and CEM cells was compared with that in normal T cells.…”
Section: Malignant T Cells Express Abnormal Levels Of Vdcc Ca 2؉ Chanmentioning
confidence: 99%
“…In addition, the involvement of dihydropyridine receptors in the TCR-dependent Ca 2+ signaling of T H 2 cells was demonstrated [20]. The presence of both regulatory β4 and pore-forming Cav1 α1 subunits of voltage-gated Ca 2+ (Cav) channels in T lymphocytes was also shown, as well as the deleterious effects of a β4-mutation on normal T lymphocyte functioning [21]. Despite preserving some voltage-dependence the main gating mechanism of these channels appeared to be linked to TCR stimulation.…”
Section: Introductionmentioning
confidence: 95%